2023
DOI: 10.1200/jco.21.02370
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Follow-Up of KTE-X19 in Patients With Relapsed/Refractory Mantle Cell Lymphoma, Including High-Risk Subgroups, in the ZUMA-2 Study

Abstract: PURPOSE Brexucabtagene autoleucel (KTE-X19) autologous anti-CD19 chimeric antigen receptor (CAR) T-cell therapy is approved for the treatment of relapsed/refractory mantle cell lymphoma (MCL). Outcomes after a 3-year follow-up in the pivotal ZUMA-2 study of KTE-X19 in relapsed/refractory MCL are reported, including for subgroups by prior therapy (bendamustine and type of Bruton tyrosine kinase inhibitor [BTKi]) or high-risk characteristics. METHODS Patients with relapsed/refractory MCL (one to five prior thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(120 citation statements)
references
References 39 publications
7
110
0
3
Order By: Relevance
“…Tecartus, an autologous CD19‐targeting CAR T‐cell therapy, has been granted conditional marketing authorisation by the European Medicines Agency (EMA) for relapsed or refractory MCL after two lines of therapy, including a BTKi. The ZUMA‐2 study reported impressive initial responses (overall response 93%, complete response 67%) with 37% of evaluable patients in ongoing response at a median follow‐up of 35.6 months 3,4 . Overall initial responses in high‐risk disease such as pleomorphic/blastoid morphology, TP53 mutations or Ki‐67 proliferation index ≥50% appeared comparable but small numbers preclude valid conclusions.…”
Section: Nhs England Nccp Eligibility Criteria Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tecartus, an autologous CD19‐targeting CAR T‐cell therapy, has been granted conditional marketing authorisation by the European Medicines Agency (EMA) for relapsed or refractory MCL after two lines of therapy, including a BTKi. The ZUMA‐2 study reported impressive initial responses (overall response 93%, complete response 67%) with 37% of evaluable patients in ongoing response at a median follow‐up of 35.6 months 3,4 . Overall initial responses in high‐risk disease such as pleomorphic/blastoid morphology, TP53 mutations or Ki‐67 proliferation index ≥50% appeared comparable but small numbers preclude valid conclusions.…”
Section: Nhs England Nccp Eligibility Criteria Commentsmentioning
confidence: 99%
“…The ZUMA-2 study reported impressive initial responses (overall response 93%, complete response 67%) with 37% of evaluable patients in ongoing response at a median follow-up of 35.6 months. 3,4 Overall initial responses in high-risk disease such as pleomorphic/blastoid morphology, TP53 mutations or Ki-67 proliferation index ≥50% appeared comparable but small numbers preclude valid conclusions. Significant adverse events of grade 3 or higher included cytokine release syndrome (15%), neurological events (31%) and infection (32%).…”
mentioning
confidence: 99%
“…Two recent multicenter trials have shown clear clinical benefits from brexucabtagene autoleucel (brexu-cel) and liso-cel in r/r MCL. ZUMA-2 enrolled 74 patients with heavily pretreated r/r MCL, the vast majority failing or relapsing after BTKi [ 54 ]. The impressive ORR of 85% and CR of 59% seen in the intention-to-treat analysis led to FDA approval of brexu-cel for this indication ( Table 1 and Table 2 ).…”
Section: Efficacy Of Autologous Car T Cell Therapy In Lymphomamentioning
confidence: 99%
“…The difference is in the manufacturing process which in case brexucabtagene autoleucel involves the removal of CD19-expressing cells from the population of CAR-T cells [ 22 ]. In a three-year follow-up study ORR for patients with MCL was found to be 91%, while CRR was 68% [ 27 ].…”
Section: Car-t Cells Approved For Clinical Practice In the European U...mentioning
confidence: 99%